Efektivitas model pembelajaran daring berbasis tiktok - Ardiyanti, Handrini; Kustandi, Cecep; Cahyadi, Ani; Elihami, Elihami; Pattiasina, Petrus Jacob (Jurnal Komunikasi Profesional, 2021)
In an effort to prevent the Covid-19 pandemic, schools are implementing online student learning methods. This government policy is in order to break the chain of spreading Covid-19. However, in practice, there are still many teachers in schools who are still confused about implementing the online learning system because the teachers are not good at technology, so the teacher only sends assignments without explaining the material. As a result, online learning becomes ineffective which has an impact on student learning outcomes. This study aims to determine the effectiveness of the tiktok-based online learning model. The method used in this research is phenomenology. The informants in this study were the parents of students who live in East Java. The conclusion of this study is that the Tik Tok application used as a learning medium has not been fully effective. Parents consider that the Tik Tok application used in their children's learning is mostly used for playing while learning hours are still in progress. Keywords: model; learning; online; tik tok. Dalam upaya mencegah pandemi Covid-19, sekolah menerapkan metode pembelajaran siswa secara online. Kebijakan pemerintah ini dalam rangka memutus mata rantai penyebaran Covid-19. Namun dalam prakteknya masih banyak guru di sekolah yang masih bingung menerapkan sistem pembelajaran online karena gurunya kurang jago teknologi, sehingga guru hanya mengirimkan tugas tanpa menjelaskan materi. Akibatnya pembelajaran online menjadi tidak efektif yang berdampak pada hasil belajar siswa. Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran daring berbasis Tik Tok. Metode yang digunakan di dalam penelitian ini adalah fenomenologi. Informan dalam penelitian ini adalah orang tua siswa yang tinggal di Jawa Timur. Kesimpulan penelitian ini adalah bahwa aplikasi Tik Tok yang digunakan sebagai media pembelajaran belum sepenuhnya berjalan dengan efektif. Para orang tua menilai bahwa aplikasi Tik Tok yang digunakan dalam pembelajaran anak-anak mereka lebih banyak digunakan untuk bermain ketika jam pembelajaran masih berlangsung. Kata kunci: model; pembelajaran; daring; tik tok.